Кримінальна субкультура як фактор радикалізації середовища засуджених до позбавлення волі - Черевко, К. О.; Cherevko, K. O.; Кирило Черевко (Європейські перспективи. - 2023. - № 2. - С. 185-191, 2023)
Наголошено, що однією з проблем складного криміногенного стану в Україні у великій мірі пов’язано із засиллям норм кримінальної субкультури. Становлення нового, сучасного суспільства передбачає вихід країни із стану криміналізму, підвищення культурного, особливо правового рівня громадян, зниження загального рівня злочинності, боротьба із найнебезпечнішими проявами кримінальної протиправності та криміногенним впливом на громадян, одним з яких є велике поширення норм кримінальної субкультури в суспільстві.

The development of a democratic independent state at the present stage of society’s development is associated with certain difficulties in all spheres of public, political, economic and social life. One of these problems is the complex criminogenic situation in Ukraine, which is largely due to the dominance of criminal subculture norms. The formation of a new, modern society involves the country’s exit from the state of criminalism, raising the cultural, especially legal level of citizens, reducing the overall crime rate, combating the most dangerousmanif estations of criminal unlawfulness and criminogenic impact on citizens, one of which is the widespread norms of criminal subculture in society. The relevance of the research topic is determined by the need for theoretical understanding and development of a sound approach to the analysis of socio-cultural issues related to the impact of criminal subculture on various segments of the culture of modern Ukraine. The formation of the criminal subculture took place within the framework of the penitentiary system, the models and principles of which were formulated by the judicial systems of European and North American states in the eighteenth century and later spread in Ukraine. The values and practices of the criminal subculture that emerged were designed to support interaction between individuals in prisons. However, in today’s reality, elements of the criminal subculture have overcome the geographical and social boundaries of prisons and have become part of various spheres of life: media, political, and everyday discourses are full of examples of the use of rituals, traditions, and expressions that are part of the criminal subculture. The level of criticism by NGOs and educational institutions aimed at reducing the influence of criminal subculture is quite high, but most often the criticism is formal and rhetorical and does not reveal the essence of the problem of its spread. The mechanisms that have allowed the values and practices of the criminal subculture to enter both official and artistic and everyday culture remain unclear. One of the effective barriers to the spread of criminal subculture should be the state policy in the field of penal enforcement.

Отмечено, что одной из проблем сложного криминогенного состояния в Украине в большой степени является засилие норм криминальной субкультуры. Становление нового, современного общества предполагает выход страны из состояния криминализма, повышения культурного, особенно правового уровня граждан, снижения общего уровня преступности, борьба с наиболее опасными проявлениями уголовной противоправности и криминогенным влиянием на граждан, одним из которых является широкое распространение норм криминальной субкультуры в обществе.
Keywords: установа виконання покарань; засуджені; кримінальна субкультура; кримінальний радикалізм; детермінація; протидія злочинності; penitentiary institution; convicts; criminal subculture; criminal radicalism; determination; counteraction to criminality; учреждение исполнения наказаний; осужденные; криминальная субкультура; криминальный радикализм; детерминация; противодействие преступности